Factors Influencing Academic Staff’s Intention to Invest in Financial Markets: Extending the Theory ofReasoned Action - Meor Azim; Mohd Hussin, Mohd Yahya; Muhammad, Fidlizan (Management Research Journal, 2024)
This study aims to understand the factors influencing investment intentions among Sultan Idris Education University (UPSI) academic staff by extending the Theory of Reasoned Action (TRA) with knowledge and awareness variables. A quantitative survey design was used, collecting data from 300 randomly selected respondents via Google Forms. The data were analyzed using exploratory factor analysis, Pearson correlation, and multiple linear regression (MLR) with SPSS version 26.0. The findings show that attitude, subjective norms, knowledge, and awareness significantly relate to investment intentions. Pearson correlation analysis revealed strong relationships between attitude and investment intention (r = - 0.437, r = - 0.437), subjective norms (r = 0.439, r = 0.439), and awareness (r = 0.689, r = 0.689), while knowledge showed a weaker significant relationship (r = - 0.215, r = - 0.215). Multiple linear regression confirmed that these factors are primary predictors of investment intention, with awareness exerting the strongest influence (β = 0.554, p<0.01, β = 0.554, p<0.01). The study suggests that increasing awareness and knowledge about investments can positively influence academic staff’s investment intentions, highlighting the need for enhanced education and awareness initiatives. It contributes empirically to consumer behavior literature in investment contexts, offering insights for investment service providers, policymakers, and investors. Additionally, it makes theoretical contributions by illustrating how knowledge and awareness influence investment intentions, helping policymakers develop policies that enhance financial literacy and support informed investment decisions.